THE INFLUENCE OF HEADMASTER LEADERSHIP AND ENVIRONMENT TOWARD COMPETENCY OF TEACHERS IN MUHAMMADIYAH PRIMARY SCHOOL IN BONTONOMPO, GOWA - Juhamri Juhamri (JICSA : Journal of Islamic Civilization in Southeast Asian, 2020)
This research examines the influence of headmaster leadership as well its circumstances toward the competence of teachers in Muhammadiyah Primary school. It employs a quantitative research methodology. The results of the questionnaire processed show that the influence of the leadership of the head of the madrasah and the madrasah environment together on the professional competence of Madrasah Ibtidaiyah Muhammadiyah teachers in Bontonompo and South Bontonompo Districts, Gowa Regency is not positive. However, the researchers suggest that the influence of the Leadership of Madrasah Principals on Professional Competence is positive. The results of this study are related to Muhammad Surya's theory which states that the school environment includes living objects in the form of the closest human being in the form of the closest human that surrounds him, namely the family. Family is the main and first educational environment because humans get education for the first time from the family environment before knowing other environments.